Sustained socio-economic inequalities in hospital admissions for cardiovascular events among people with diabetes in England - Shather,Z; Laverty,A; Bottle,RA; Watt,H; Majeed,FA; Millett,CJ; Vamos,EP (The American Journal of Medicine, 2018)
ObjectiveThis study aimed to determine changes in absolute and relative socio-economic inequalities in hospital admissions for major cardiovascular events and procedures among people with diabetes in England.MethodsWe identified all patients with diagnosed diabetes aged ≥45 years admitted to hospital in England between 2004-2005 and 2014-2015 for acute myocardial infarction, stroke, percutaneous coronary intervention (PCI) and coronary artery bypass graft (CABG). Socio-economic status was measured using Index of Multiple Deprivation. Diabetes-specific admission rates were calculated for each year by deprivation quintile. We assessed temporal changes using negative binomial regression models.ResultsMost admissions for cardiovascular causes occurred among people aged ≥65 years (71%) and men (63.3%), and the number of admissions increased steadily from the least to the most deprived quintile. People with diabetes in the most deprived quintile had 1.94-fold increased risk of acute myocardial infarction (95% CI 1.79-2.10), 1.92-fold risk of stroke (95% CI 1.78-2.07), 1.66-fold risk of CABG (95% CI 1.50-1.74), and 1.76-fold risk of PCI (95% CI 1.64-1.89) compared with the least deprived group. Absolute differences in rates between the least and most deprived quintiles did not significantly change for acute myocardial infarction (P=0.29) and were reduced for stroke, CABG and PCI (by 17.5, 15 and 11.8 per 100,000 people with diabetes, respectively, P≤0.01 for all).ConclusionsSocio-economic inequalities persist in diabetes-related hospital admissions for major cardiovascular events in England. Besides improved risk stratification strategies considering socio-economically defined needs, wide-reaching population-based policy interventions are required to reduce inequalities in diabetes outcomes.